The Relationship between Headteachers’ Supervision of Professional Documents and Academic Performance in Primary Schools in Embu and Murang’a Counties - Muchiri Jane Muthoni; Margaret Wanjiru Gitumu; John Mwaruvie (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
Supervision is a vital administrative tool employed by headteachers in ensuring teachers’ effectiveness and competence in teaching and learning in schools. Over time, pupils’ academic performance in examinations has been consistently low in public primary schools and has created concern among education stakeholders in Kenya and the world over. The objective of this study is assess the relationship between headteachers’ supervision of professional documents and academic performance in primary schools in Embu and Murang’a counties. A descriptive survey research design was used. The target population was 14,786 respondents; simple random sampling was used to select 256 of these. Data were collected using questionnaires, interviews and an observation checklist. To ascertain reliability, the instrument was piloted, and Cronbach’s alpha coefficient was calculated as 0.93. The data were analysed using descriptive statistics involving frequencies, percentages, means and standard deviations and inferential statistics, precisely, correlation. The results show that the development of professional documents was common in primary schools and that the best documents supervised by headteachers were schemes of work. The null hypothesis tested was not rejected based on the correlation of r=-.044<0.05 and P=0.732>0.05 between headteachers’ supervision of professional documents and academic performance. The study recommends that headteachers should guide teachers on the importance of consistency in professional documents. However, headteachers’ supervision of teachers’ preparation of professional documents did not impact positively on pupils’ academic performance at KCPE in Embu and Murang’a counties. The findings of the study will serve as a reference for similar studies in education administration and management.